CONFLICTS AND REPERTORIES OF ORGANIZATION OF CHILEAN REFUGEES IN BUENOS AIRES (1973-1983) - Casola, Natalia (Revista de Historia Social y de las Mentalidades, 2024)
This article describes and analyzes the experiences of Chilean refugees in the refuge houses of the Capital Federal Capital and Greater Buenos Aires under the orbit of the Argentine Commission for Refugees (CAREF) between 1973 and 1983. The starting point is the he asked about the effects of the repressive context, to answer what it meant to be a refugee in Argentina during the third Peronist government and the military dictatorship. Likewise, after confirming that refugee status brought into play new family dynamics and forms of community-based coexistence, conflicts are analyzed as well as the processes of building solidarity ties and it is shown that they had different expression in men and women.